ESTIMATION OF CO-BENEFITS IN RESPONDING TO PRIVATE VEHICLE RESTRICTION POLICIES IN TRANSIT-ORIENTED AREAS (CASE STUDY: DKI JAKARTA PROVINCE) - Pramoe Izdihar, Rakan
The high dominance of private vehicle usage leads to externalities for an urban area, including traffic congestion, especially during peak hours, increased pollution, and urban population health issues. Policy-making to minimize these externalities is crucial in the current context, particularly in response to the global goal of reducing emissions to net zero by 2050. Recently, the co-benefits approach has been considered in decision-making within the transportation sector. The importance of co-benefits is highly promoted alongside mitigation strategies for greenhouse gas reduction, particularly for cities in developing countries facing three main challenges: development, environmental pollution, and climate change adaptation (Puppim De Oliveira, 2013). The co-benefits approach creates optimal situations by considering both local and global advantages. This study aims to estimate the co-benefits of private vehicle restriction policies in Jakarta with three main objectives: identifying policies, calculating modal shifts, and estimating avoided emissions. The analysis is conducted using the multinomial logit approach, and emission calculations are based on IPCC guidelines and the EMISI tool from WRI. The study results indicate that the Vehicle Restriction Policy (VRP) significantly impacts modal shifts from private vehicles to public transportation. The avoided emissions through travel calculations can reach up to 57%. Significant independent variables influencing mode choice include travel costs, travel time, distance, income level, and education level. The findings of this study support the